Phase transition of LaMnO3 nanoparticles prepared by microwave assisted combustion method. (January 2019) - Tran, Thi Ha; Bach, Thanh Cong; Pham, Nguyen Hai; Nguyen, Quang Hoa; Sai, Cong Doanh; Nguyen, Hoang Nam; Nguyen, Viet Tuyen; Nguyen, Trong Tam; Ho, Khac Hieu; Doan, Quoc Khoa
Abstract: LaMnO3 nanopowder was synthesized by the combustion method assisted with microwave irradiation using alanine as fuel and metal nitrate as the oxidant. The effect of fuel/oxidant molar ratio (F ratio) on the structure and morphology of the product was studied. The as-produced nanopowder was characterized by Xray diffraction measurement, scanning electron microscopy, energy dispersive spectroscopy, and Raman spectroscopy. SEM images shows that pure, fine nanopowder with an average particle size of 40 nm was obtained while XRD results revealed that the hexagonal or orthorhombic structure of LaMnO3 nanopowder could be selected by adjusting the amount of fuel. An order-disorder phase transition was also observed by Raman spectroscopy at low temperature under laser heating.